THAI STUDENT ONLINE RESPONSES TO NATIVE SPEAKER TOWARD INDONESIAN LANGUAGE LEARNING FOR FOREIGN SPEAKERS COURSE (RESPON MAHASISWA THAILAND DALAM PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) DENGAN PENUTUR ASLI SECARA ONLINE) - Robertus Pujo Leksono; Refa Lina Tiawati (Universitas PGRI Sumatera Barat, 2020)
Thai student responses to Indonesian online learning with native speakers. The problem in this research is how Thai learners respond to learning Indonesian (BIPA) online with native speakers. And how is the online learning process provided by teachers and guest lecturers from STKIP PGRI West Sumatra, UPI Language Center, BPK Penabur School with the theme of learning is about introductions, family, and about the song Indonesia Raya. The purpose of conducting this research is to obtain an overview of how the response of Thai learners who study at NU to learning Indonesian online taught by natives. The method in this study uses two forms of research methods, namely the first library research method and the second with descriptive analysis with the technique used is to observe and give questionnaires to respondents and teachers about how to respond and their satisfaction in learning Indonesian natively. . The results show that this learning process improves Indonesian learning outcomes and increases the number of vocabulary it gets. As well as the response of Thai students who interact with natives shows the character of speaking well, by repeating the same theme twice at different times to practice speaking with Indonesians